2023
DOI: 10.1007/s10526-023-10222-5
|View full text |Cite
|
Sign up to set email alerts
|

Biological enhancement of the cover crop Phacelia tanacetifolia (Boraginaceae) with the nematophagous fungus Pochonia chlamydosporia to control the root-knot nematode Meloidogyne hapla in a succeeding tomato plant

Jana Uthoff,
Desiree Jakobs-Schönwandt,
Jan Henrik Schmidt
et al.

Abstract: Root-knot nematodes cause global economic losses in a wide range of crops. We investigated the potential of seed coatings of the cover crop Phacelia tanacetifolia (Boraginaceae) when inoculated with the nematophagous fungus Pochonia chlamydosporia (Hypocreales: Clavicipitaceae) to protect subsequently grown tomato plants from root galling caused by the root-knot nematode Meloidogyne hapla (Tylenchida: Meloidogynidae). Therefore, seeds of P. tanacetifolia were coated with P. chlamydosporia blastospores and plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…A previous study with the seed treatment described in this study has already shown its efficiency. Uthoff et al [20] demonstrated the efficacy of P. chlamydosporia in the seed treatment against the root-knot nematode Meloidogyne hapla. P. chlamydosporia in seed treatment reduced the total number of M. hapla eggs by up to 95.6% in greenhouse experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study with the seed treatment described in this study has already shown its efficiency. Uthoff et al [20] demonstrated the efficacy of P. chlamydosporia in the seed treatment against the root-knot nematode Meloidogyne hapla. P. chlamydosporia in seed treatment reduced the total number of M. hapla eggs by up to 95.6% in greenhouse experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Pochonia chlamydosporia strain Pc001, deposited in the fungal culture collection at the Julius Kühn Institute, was originally isolated from surface-sterilized cysts of Heterodera schachtii collected from sugar beet fields located in North Rhine-Westphalia, Germany [19]. P. chlamydosporia was cultivated according to Uthoff et al [20]. To this end, chlamydospores cultivated on potato dextrose (PDA, 39 g/L, Carl Roth GmbH & Co. KG, Karlsruhe, Germany) at 23 • C were used as pre-culture inoculum for blastospore cultivation.…”
Section: Pochonia Chlamydosporia Blastospore Cultivationmentioning
confidence: 99%